An Analysis of the Use of the Filipino Language in the Technical Vocational and Livelihood Track: Towards the Development of a Proposed Language Policy Framework in Technical Education - Lansang, Kelvin G.; Zamora, Niña Christina L. (Journal of Technical Education and Training, 2025)
This study examines the role of the Filipino language—both academic and modern—in shaping a language policy framework for Technical Vocational and Livelihood Education (TVLE) in Senior High School. Recognizing the increasing demand for linguistic accessibility in technical education, this research investigates how Filipino facilitates comprehension, communication, and instructional efficiency in specialized TVL subjects. The study involved a comprehensive dataset comprising 1,953 TVLE students from Grades 11 and 12, 48 teachers, 8 school administrators, and 8 education and TVLE experts across nine cities in Metro Manila. A mixed-methods approach was employed, utilizing observations, questionnaires, and interviews to analyze the frequency, nature, and impact of Filipino language usage in TVL instruction. Findings indicate a strong consensus on the effectiveness of the Filipino language as a medium of instruction, particularly in enhancing student engagement, knowledge retention, and skill acquisition. Observations highlighted prevalent code-switching between English and Filipino, reflecting the adaptive strategies employed by both teachers and students. Various translation techniques, including direct and literal translations, were identified as essential for bridging gaps in technical vocabulary. The results further suggest that using Filipino in TVL subjects fosters a more inclusive and contextually relevant learning environment, enabling students to grasp complex technical concepts with greater ease. Based on these findings, the study proposes the TVLE+ Language Policy, which formalizes the integration of Filipino as a primary instructional language in TVL courses while maintaining bilingual flexibility for technical terminologies and global competency. This policy aims to standardize language use in technical education, ensuring pedagogical effectiveness and linguistic inclusivity. The implications of this research extend beyond language instruction, contributing to broader discussions on curriculum development, language policy reform, and the role of native languages in vocational education.